2017
DOI: 10.4172/2157-7099.1000457
|View full text |Cite
|
Sign up to set email alerts
|

Three Cases of Major Depression: Different Pharmacological Antidepressant Options

Abstract: Three cases with different forms of major depression and different pharmacological antidepressant treatments are presented. In the first case report, citalopram, a selective serotonin reuptake inhibitor, improved transient depressive symptoms in a professionally busy man who recovers from the depressive symptoms and solves the social problems in his team. In the second case report showing a severe form of major depression and a suicide attempt, the tricyclic antidepressant drug doxepin failed to improve depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…In the case report -Three Cases of Major Depression: Different Pharmacological Options, the authors Werner and Covenas [9] describe a different severity of major depression in three cases, which require a totally different pharmacological treatment. The authors already reported about a multimodal pharmcotherapy in major depression (J Cytol Histol 2014; 5: 4).…”
Section: In the Research Article Spermatocyte Spreading During Meiotimentioning
confidence: 99%
“…In the case report -Three Cases of Major Depression: Different Pharmacological Options, the authors Werner and Covenas [9] describe a different severity of major depression in three cases, which require a totally different pharmacological treatment. The authors already reported about a multimodal pharmcotherapy in major depression (J Cytol Histol 2014; 5: 4).…”
Section: In the Research Article Spermatocyte Spreading During Meiotimentioning
confidence: 99%